Slit-scan - Figueiredo, Luís Miguel Ribeiro da Silva Cabral (2011)
The processing of the digital image brought new ways for all the known media to adapt to this new reality. The study of the digital media is not yet over and is to prove that the slit-scan technique still has many ways to develop that we create this study. We present the state of the of the slit-scan technique, not forgetting to mention the history of the image registration till it gets to the digital world. It’s also needed to present the concept of movement that is one of the most important subjects about slit-scan. Guestbook, the project made for the Master in Sound and Image will also be presented as it was developed side by side, using the same subject and investigation. In the end some research will be presented, identifying the development of some techniques and it’s results. During the research and the Dissertation some questions were tried to answer: -What is slit-scan and what is it useful for? -How can we use slit-scan in Science or in Art? -In how many ways can we use this technique and in what do they result? -Are there any new ways to progress with the slit-scan technique?